MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
Menu
shubham mishra Grade: 11
        

1/b-c  + 1/b-a  =  1/a  +  1/c

5 years ago

Answers : (2)

Latika Leekha
askIITians Faculty
165 Points
										

I am not able to interpret your query. Please write down the problem clearly so that I can provide you the meaningful answer.


Thanks & Regards


Latika Leekha


askIITians faculty

3 years ago
SHAIK AASIF AHAMED
askIITians Faculty
74 Points
										
Hello student,
a, b, c are in HP, so 1/a, 1/b, 1/c are in AP,

->2/b - 1/a = 1/c

->(2a - b) / ab = 1/c

->c = ab/(2a - b)

=1/(b-a) + 1/(b-c)
= 1/(b-a) + 1/(b - ab/(2a - b) )

= 1/(b-a) + (2a - b)/( b(2a - b) - ab)

= 1/(b-a) + (2a - b)/ { b(2a - b - a) }

= 1/(b-a) + (2a - b) / {b ( a - b) }

= 1/(b-a) - (2a - b) / {b(b-a) }

= (b - (2a - b) )/ ( b(b-a) )
=(2b - 2a)/(b(b-a))
= 2(b-a)/(b(b-a)) = 2/b=1/a+1/c
Hence (1/b-c)+(1/b-a)=1/a+1/c
Thanks and Regards
Shaik Aasif
askIITians faculty
3 years ago
Think You Can Provide A Better Answer ?
Answer & Earn Cool Goodies
  • Complete JEE Main/Advanced Course and Test Series
  • OFFERED PRICE: Rs. 15,900
  • View Details

Ask Experts

Have any Question? Ask Experts

Post Question

 
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!! Click Here for details